(untitled) (Research, Society and Development, 2021)
Parkinson’s disease is the second most common neurodegenerative disease in the world, with tremor being one of its main symptoms. The existing treatments for tremors have several restrictions and side effects that end up limiting their use. Thus, the idea of alternative treatments, using engineering, arises, which are less invasive and without side effects. The scope of this work will be to present and discuss the main solutions involving engineering for the reduction of pathological tremors that have been found in recent years. For the purpose of following a research methodology, keywords were used to perform searches in some of the main scientific databases, and with some filters applied it was possible to identify 26 articles dealing with the topic we wish to study. As a result, it was possible to notice a considerable increase in the study of the subject in recent years and to observe the existence of 4 categories of alternative treatments: functional electrical stimulation (FES), mechanical actuators, damped systems, and intelligent materials. After the research, it was concluded that the solutions using FES and mechanical actuators were the most studied and those that are in more advanced stages of testing, having products on the market that use FES as a treatment for pathological tremors.